PENILAIAN KINERJA PADA BMT AL-KAMAL TAHUN 2012 – 2014 - Ika Neni Kristanti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2016)
The study aims to determine the health level BMT AL-Kamal years 2012-2014 based on the Regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No.20 / Per / M. KUKM / XI / 2008 menyangkutatas capital, asset quality, management, liquidity, efficiency, independence and growth as well as the identity of cooperatives. This research is a descriptive evaluative research.The subjects were BMT AL-Kamal in which the object of evaluation is the health of BMT AL-Kamal. Data analysis techniques in this study using descriptive analysis. In this study, data were collected through the method of documentation and interviews. The conclusion that can be drawn through the measurement results that have been made known that the performance BMT AL-Kamal Kebumen overall still unwell. It can be seen from the scores BMT AL-Kamal, 2012, 2013, 2014 scored 41.3, 39.9 and 42.55 Keywords: health leve, Kooperative Identity and Kooperatie